2004
DOI: 10.1111/j.1365-2958.2003.03957.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular architecture of the Cryptococcus neoformans capsule

Abstract: SummaryMany microbes are surrounded by phagocytosisinhibiting capsules. We took advantage of the large size of the polysaccharide capsule of the pathogenic yeast Cryptococcus neoformans to examine capsular architecture and the relationship between molecular architecture and the interaction of the capsule with potentially opsonic serum proteins. Our experimental design used complementary approaches in which (i) assessment of permeability to macromolecules of different Stokes radii; (ii) determination of the bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
136
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(146 citation statements)
references
References 31 publications
(46 reference statements)
6
136
0
1
Order By: Relevance
“…Indeed, monoclonal antibodies to GXM recognize cellassociated GXM and exopolysaccharide (31,63), and the ultrastructure visible in freeze-fracture images of the capsule (53) and STEM images of exopolysaccharide are similar in appearance, suggesting structural relatedness. Furthermore, the capsule contracts in response to the presence of salt (57,67), as expected given the viscoelastic properties demonstrated in this work of a polyelectrolyte molecule. The overlapping of individual polysaccharide molecules to expand the thickness of the capsule may involve either an increase in GXM production or the synthesis of GXM polymers with a higher attraction to existing fibers.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…Indeed, monoclonal antibodies to GXM recognize cellassociated GXM and exopolysaccharide (31,63), and the ultrastructure visible in freeze-fracture images of the capsule (53) and STEM images of exopolysaccharide are similar in appearance, suggesting structural relatedness. Furthermore, the capsule contracts in response to the presence of salt (57,67), as expected given the viscoelastic properties demonstrated in this work of a polyelectrolyte molecule. The overlapping of individual polysaccharide molecules to expand the thickness of the capsule may involve either an increase in GXM production or the synthesis of GXM polymers with a higher attraction to existing fibers.…”
Section: Discussionsupporting
confidence: 51%
“…More recently, antibody penetration studies have suggested that capsular regions more distal from the cell wall also have an increased density in enlarged capsules, and capsule phenotype studies have suggested the formation of a new GXM structure at the periphery of the capsule (24,57). Although the data presented cannot distinguish between different modes of capsule growth, a capsule construction model dependent on the self-association of GXM does unify several observations.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Several models could explain this apparent discrepancy. A modification in epitope accessibility could be due to changes in capsule density under different growth conditions 32 and experimental designs. In addition, the localization of a new structure outside the old one, as seen here, could also be related to the degradation of the initial structure by local factors or by aging.…”
Section: Discussionmentioning
confidence: 99%